Substance Use and Depressive Symptoms Among Adolescents Treated in a Pediatric Emergency Department. Issue 2 (3rd March 2016) - Hernandez, Lynn; Cancilliere, Mary Kathryn; Graves, Hannah; Chun, Thomas H.; Lewander, William; Spirito, Anthony
ABSTRACT: The current study examined associations between substance use and depressed mood by gender and type of substance used (no use, alcohol, marijuana, or both alcohol and marijuana) in a sample of 713 adolescents ( M age = 15.3) recruited from a Pediatric Emergency Department (PED). Adolescents who reported any marijuana use had higher overall depressed mood scores compared to all other adolescents. When examined by gender, females with both alcohol and marijuana use reported the highest overall depressed mood symptoms. These results suggest the usefulness of screening and identification of depressive symptoms among adolescents presenting to a PED for substance use-related problems.